Advances in traditional production of panela in Colombia: analysis of technological improvements and alternatives (2018)
(Eng) Panela, or unrefined non centrifugal brown sugar, is a natural sweetener obtained from the evaporation and concentration of sugarcane juice (Saccharum officinarum), essential for food security, agricultural economics and rural development in Latin America. The degree of process efficiency and the marketing evaluation for this product in Colombia is as yet incipient. This study presents the traditional system for panela production, from a technical and engineering perspective, also highlighting some aspects of qual - ity and innovation. Improvements to the traditional furnace design, extraction and milling, clarification, and heat transfer are analyzed. By criteria of competitiveness and efficiency, was evidenced the need to continue the development and transfer of innovative technological alternatives. It is also imperative the participation of the panela producers in new and potential markets.